POLICY ON THE LEGAL REGULATION OF CRIMINAL ACTS INVOLVING THE MISUSE OF ARTIFICIAL INTELLIGENCE DEEPFAKES - Amalia Andayani Nugraha; Faizin Sulistio; Patricia Audrey Ruslijanto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The development of artificial intelligence (AI) technology has brought significant advances in various areas of human life, but on the other hand, it has also created new challenges in the legal field, especially through the emergence of deepfake technology. Deepfake technology utilizes AI to manipulate images, videos, and voices of individuals to appear realistic, which in practice is often misused for purposes such as fraud, pornography, spreading hoaxes, and damaging reputations. Indonesia currently has no specific regulations governing the misuse of deepfake technology, so law enforcement still relies on general provisions such as the Criminal Code, the Electronic Information and Transaction Law, the Personal Data Protection Law, and the Sexual Violence Criminal Law. This legal vacuum or incompleteness causes legal uncertainty and potential violations of the principle of legality. Through a criminal law policy approach, adaptive legal reforms are needed to keep pace with developments in digital technology. Efforts that can be made include revising the Electronic Information and Transaction Law as lex specialis that regulates provisions on deepfakes or formulating specific regulations on artificial intelligence (AI) that comprehensively regulate ethical aspects, responsibility, and criminal liability. This policy is expected to provide certainty, justice, and protection of individual rights in facing the legal challenges of the digital era in Indonesia.